Lingkungan Biofisik Hutan Mangrove di Kota Langsa, Aceh - Iswahyudi, Iswahyudi; Kusmana, Cecep; Hidayat, Aceng; Noorachmat, Bambang Pramudya (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
Mangrove ecosystem is an area that serves as a interface between the land and sea, but at the moment has a lot of damage. The phenomenon of damage to the mangrove forest ecosystem also occurred in Langsa City. This study aims to analyse biophysical conditions of mangrove forest ecosystems in Langsa City. The method used in this study is to combine qualitative and quantitative descriptive approaches. Results of the study show that the area of mangrove forest in the study has increased as large as 324.29 ha in the period of 6 years (2007-2013). The mangrove flora in Langsa City consist of a group of true mangrove flora and mangrove associates, consisting of 14 families and 25 species. The criticality of mangrove forests in the research location is classified as damaged (1,955.96 ha) and severely damaged (2,556.82 ha).